Eventos feriales agroindustrial: Plan parcial desarrollo urbano Alameda socioempresarial municipio de Sopó (2017)
This work deals with the problem that is currently being experienced throughout the territory of Cundinamarca because of the growth of the capital that is being set in the agricultural lands harms the entire population, economy, and quality of life. Solving with new concept of city and an architectural project that helps to give a 360 ° turn to the problem